Helmet and reflective clothing use among motorcyclists in Kenya: a survey of use, knowledge, attitudes, and practices in two districts. (7th October 2012) - Bachani, AM; Pereira, S; Mogere, S; Herbert, HK; Akungah, D; Maina, W; Stevens, K; Hyder, AA
Abstract : Background: Road traffic injuries (RTIs) contribute to a significant proportion of the burden of disease in Kenya. Motorcycle-related RTIs are a significant contributor to this burden. Aims/Objectives/Purpose: This study assesses helmet wearing and reflective clothing usage, and knowledge, attitudes and perceptions around their use in Thika and Naivasha districts in Kenya. Methods: Between August 2010, and December 2011, we conducted 4 rounds of observational studies; 2 rounds of roadside knowledge, attitude and perceptions (KAP) surveys; 4 focus group discussions (FGDs); and, a community based household survey in each district. Results/Outcomes: While the majority of participants in FGDs, and KAP surveys acknowledged the life saving potential of helmets, less than one third of all drivers in Thika and Naivasha wore helmets while driving motorcycles. Helmet usage among passengers was even lower (<2%) in both districts. Reflective clothing usage shows a large disparity between the two districts, with the 34% and 56% of observed motorcyclists in using reflective clothing in Thika and Naivasha respectively. Use of reflective clothing by passengers in both districts was extremely low. The most common reason cited for lack of helmet use was because it was considered inconvenient or uncomfortable. The majority of respondents indicated they did not wear reflective clothing because they did not have it. Significance/Contribution to the Field: This study establishes low usage of helmets and reflective clothing in the two districts in Kenya. It highlights areas for policy and programmatic focus such as enhanced enforcement, legislation, and social marketing to reduce motorcycle related injuries and deaths.